Contemporary perspectives on research on coronavirus disease 2019 (COVID-19) in early childhood education - Saracho, Olivia N. (Emerald Publishing Limited : Information Age Publishing, Inc., 2022)
Coronavirus Disease 2019 (COVID-19), which is also known as SARS-CoV-2, has had a great impact in early childhood education programs. Since the effect of this epidemic was new, and little research had been conducted, this volume is devoted to understanding mutual and contemporary themes in the impact of Coronavirus Disease 2019 (COVID-19) in early childhood education. Early childhood education (ECE) centers encountered unprecedented challenges due to the COVID-19 crisis. Comprehensive reviews of the literature, descriptions of programs or situations, and research studies provided accounts of current situations in early childhood education including programs and individuals who were working with young children whose ages ranged from birth to eight years of age. The chapters in this special volume discuss how early childhood education faced unprecedented challenges due to the COVID-19 crisis and demonstrate the breadth and theoretical effectiveness of this domain. This volume provides a brief introduction that acknowledges the valuable contributions of these chapters to the impact of this pandemic in early childhood education and offers a valuable tool to practitioners and researchers who are conducting studies on the impact of COVID-19.At the beginning of the year 2020, after a December 2019 outburst in China, the World Health Organization acknowledged SARS-CoV-2 as a different kind of coronavirus. It immediately multiplied around the world, mostly through person-to-person contact. Infections ranged from mild to deadly. COVID-19 can cause a respiratory tract infection such as ones sinuses, nose, and throat or lower respiratory tract such as ones windpipe and lungs (World Health Organization, 2020a). On January 30, 2020, the World Health Organization (WHO) affirmed that COVID-19 had become a public health emergency causing an international problem. By March 12, 2020, everybody was aware of this pandemic. It also created an understanding about this first-time consciousness in research about this disease, which generated an immense publication production. It also became the basis for this special volume.
Keywords: Early childhood education.; Early childhood teachers -- Training of.; School crisis management.; COVID-19 Pandemic, 2020-2023 -- Social aspects.; Education -- Schools -- Levels -- Early Childhood (incl. Preschool & Kindergarten); Early childhood care and education.; Pre-school and kindergarten.; elektronické knihy; electronic books